Periodontal diagnosis in private dental practice: a case‐based survey. (June 2016) - Bailey, DL; Barrow, S‐Y; Cvetkovic, B; Musolino, R; Wise, SL; Yung, C; Darby, I
Abstract: Background: Despite the prevalence of periodontitis in Australia, there are few reports regarding periodontal diagnosis and therapies in the general dental practice setting. This study aimed to assess the degree of diagnostic accuracy in periodontal cases of Victorian general dental practitioners. Methods: Following ethics approval, dentists were invited to complete a scenario‐based questionnaire on the Australian Dental Association Victorian Branch (ADAVB) website. Five text‐based clinical scenarios (from a total of 10) were randomly presented, representing patients with a range of disease levels from periodontal health/gingivitis to severe periodontitis, and respondents were asked what examinations they would usually perform. Based upon the presented results of periodontal and radiographic examinations, a periodontal diagnosis was requested. Results: One hundred and thirty‐five dentists attempted the survey. Most were in group practice and based in Melbourne; 22.5% of respondents worked in a practice employing a hygienist. The clinical parameters most commonly measured to diagnose periodontal disease were pocket depth and mobility. The majority of respondents diagnosed health, gingivitis and mild periodontitis correctly compared to American Academy of Periodontology guidelines. However, moderate periodontitis tended to be diagnosed as severe. Conclusions: Dentists in Victoria used appropriate clinical parameters when assessing periodontal disease and were generally accurate in their diagnoses. There is a need for consensus regarding diagnostic definitions.